Development of a smart scaffold for sequential cancer chemotherapy and tissue engineering - Sengupta, Poulomi; Agrawal, Vinay; Bhagavatula L. V. Prasad (ACS Omega, 2020)
The fabrication of a dual-functional drug-containing porous polymeric scaffold by layer-by-layer surface modification involving citrate-stabilized gold nanoparticles and cisplatin molecules is being reported. These scaffolds were characterized by electron microscopy and X-ray photoelectron spectroscopy. The capability of the scaffolds to release hydrated cisplatin in a slow and sustained manner over two days is established. Most importantly, the scaffolds turn nontoxic and cell-friendly after drug release, thus allowing the noncancerous fibroblast cells to adhere and proliferate (from 5000 cells to 16,000 cells in 6 days), becoming a potential solution toward an effective drug-carrying scaffold for volume-filling applications. The scaffold-mediated cancer cell killing and fibroblast cell proliferation were confirmed by fluorescence microscopy imaging, flow cytometry, and cell proliferation assays. We surmise that such a dual-purpose (drug-delivery and volume-filler) scaffold could help avoid the multiple surgical interventions needed for tumor surgery and cosmetic corrections. To the best of our knowledge, this is the first example of scaffolds with such a dual functionality which gets manifested in a sequential manner.